HISTORICAL FEATURES LEGAL EDUCATION IN RUSSIA AT THE TURN XIX-XX СENTURIES - D V Rubinstein (RUDN Journal of Russian History, 2014)
The article examines the main directions of development of legal education in Russian and foreign universities and legal departments of the Russian Empire. Particular attention is paid to the analysis of the "educational immigration" when, due to various reasons from Russia traveled thousands of young men and women to study at European universities. In this regard, the author analyzes the four streams of student immigration to Europe, which cover the period from the beginning of the 1860s until 1914. The author emphasizes that the outflow of young people in the universities of Europe was so great that in the European countries have begun to express concern about "dominance" of immigrants from the Russian Empire. In this regard, the article shows the introduction of the Russian youth stringent restrictive measures. Next to specific material creates in Russian and foreign universities in various legal organizations of Russian students and proved that a considerable part of Russian students, educated in European universities, intellectually bound intellectuals Russia and Europe.